A review on successful approaches of converting adult somatic cells into induced pluripotent stem cells (iPSCs) - Islam, Tashfia (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.